2017
DOI: 10.1007/s00125-017-4373-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin and exercise training on FGF21, its receptors and target genes in obesity and type 2 diabetes

Abstract: Insulin-induced expression of muscle FGF21 correlates strongly with a rise in serum FGF21, and this response appears intact in overweight/obesity and type 2 diabetes. FGF21 resistance may involve reduced KLB expression in WAT. However, increased FGFR1c expression or other mechanisms seem to ensure adequate expression of most FGF21 target genes in WAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 50 publications
11
59
0
Order By: Relevance
“…Moreover, circulating FGF21 and CHI3L1 correlated positively with fasting plasma glucose and HbA1c, but inversely with insulin sensitivity in the total study cohort. These findings are consistent with several other studies, which has demonstrated elevated circulating levels of FGF21 and CHI3L1 in patients T2D (Nielsen et al 2008;Chavez et al 2009;Cheng et al 2011;Kruse et al 2017). However, in contrast to our hypothesis, these alterations did not attenuate the exerciseinduced regulation of these myokines in the muscle or the circulation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, circulating FGF21 and CHI3L1 correlated positively with fasting plasma glucose and HbA1c, but inversely with insulin sensitivity in the total study cohort. These findings are consistent with several other studies, which has demonstrated elevated circulating levels of FGF21 and CHI3L1 in patients T2D (Nielsen et al 2008;Chavez et al 2009;Cheng et al 2011;Kruse et al 2017). However, in contrast to our hypothesis, these alterations did not attenuate the exerciseinduced regulation of these myokines in the muscle or the circulation.…”
Section: Discussionsupporting
confidence: 91%
“…The role of FGF21 as a myokine was first suggested by experimental work showing increased muscle expression and release of FGF21 in Akt1 overexpressing mice (Izumiya et al 2008). This was supported by studies showing increased muscle expression and serum FGF21 levels in response to physiological concentrations of insulin in humans (Hojman et al 2009;Kruse et al 2017). However, as reported previously (Kjobsted et al 2016), serum insulin levels declined~50% immediately after exercise in our study, supporting that the increase in circulating FGF21 in response to acute exercise does not originate from skeletal muscle but rather from the liver, where it seems to be mediated by an elevated glucagon-to-insulin ratio (Hansen et al 2015a).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The NCOA1 gene in adipocytes has also been shown to be associated with metabolic disease [87][88][89]. The KSR2 gene [60,90,91] and FGF21 [92][93][94] are also integrated genes in the network associated with obesity, Figure 7 and S3. Therefore, a number of the genes and pathways identified in Figure 7 and S3 provide potential therapeutic targets for adipocytes associated with obesity and metabolic disease.…”
Section: Discussionmentioning
confidence: 95%